2019
DOI: 10.1038/s41467-019-12888-x
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and characterization of Cardiac Glycosides as senolytic compounds

Abstract: Compounds with specific cytotoxic activity in senescent cells, or senolytics, support the causal involvement of senescence in aging and offer therapeutic interventions. Here we report the identification of Cardiac Glycosides (CGs) as a family of compounds with senolytic activity. CGs, by targeting the Na+/K+ATPase pump, cause a disbalanced electrochemical gradient within the cell causing depolarization and acidification. Senescent cells present a slightly depolarized plasma membrane and higher concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
210
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(237 citation statements)
references
References 51 publications
7
210
1
1
Order By: Relevance
“…Piperlongumine -Radiation-induced senescent astrocytes in vivo -Radiation-induced cognitive dysfunction mouse model [205] -SMARCB1 downregulation-induced senescent A375 melanoma cells -Therapy-induced A549 or H358 lung cancer cells [145] -Radiation-induced, replication exhausted and Ras-induced senescent WI38 fibroblasts [206] Curcumin -Patient-derived senescent intervertebral disc cells [207] -Radiation-induced, oncogene-induced and replication-exhausted senescent WI38 fibroblasts [208] Fisetin -Replication-exhausted senescent Ercc1−/− MEFs -Therapy-induced senescent IMR90 senescent cells -Progeroid Ercc1 −/∆ mice and aged C57BL/6 mouse models -Murine and human-derived senescent adipose tissue [209] -Senescent human umbilical vein endothelial cells [210] Metformin -Murine olfactory ensheathing cells ex vivo [211] Panobinostat -Therapy-induced senescent A549 lung and FaDu head and neck cancer cells [212] 17-DMAG -Oxidative-stress-induce primary Ercc1 −/− -progeroid Ercc1 −/∆ mouse model [213] Torin 1 -Murine senescent hepatocytes ex vivo [214] Epigallocatechin gallate (EGCG) -Senescent 3T3-L1 preadipocytes [215] Bafilomycin A1 -Therapy-induced HCT116 colorectal cancer cells [158] Azithromycin and roxithromycin -Therapy-induced senescent MRC-5 and BJ human fibroblasts [216] Fenofibrate -Senescent T/C28a2 human chondrocytes [217] Cardiac glycosides -Therapy-induced senescent A549 lung cancer cells and SK-MEL-103 melanoma cells in vitro and in vivo [218,219] Several natural and synthetic compounds have been tested for their senescence-eliminating effects in a variety of disease models. The table summarizes the primary current preclinical evidence demonstrating the senolytic agent and the experimental model used.…”
Section: Senolytic Model/cell Line Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Piperlongumine -Radiation-induced senescent astrocytes in vivo -Radiation-induced cognitive dysfunction mouse model [205] -SMARCB1 downregulation-induced senescent A375 melanoma cells -Therapy-induced A549 or H358 lung cancer cells [145] -Radiation-induced, replication exhausted and Ras-induced senescent WI38 fibroblasts [206] Curcumin -Patient-derived senescent intervertebral disc cells [207] -Radiation-induced, oncogene-induced and replication-exhausted senescent WI38 fibroblasts [208] Fisetin -Replication-exhausted senescent Ercc1−/− MEFs -Therapy-induced senescent IMR90 senescent cells -Progeroid Ercc1 −/∆ mice and aged C57BL/6 mouse models -Murine and human-derived senescent adipose tissue [209] -Senescent human umbilical vein endothelial cells [210] Metformin -Murine olfactory ensheathing cells ex vivo [211] Panobinostat -Therapy-induced senescent A549 lung and FaDu head and neck cancer cells [212] 17-DMAG -Oxidative-stress-induce primary Ercc1 −/− -progeroid Ercc1 −/∆ mouse model [213] Torin 1 -Murine senescent hepatocytes ex vivo [214] Epigallocatechin gallate (EGCG) -Senescent 3T3-L1 preadipocytes [215] Bafilomycin A1 -Therapy-induced HCT116 colorectal cancer cells [158] Azithromycin and roxithromycin -Therapy-induced senescent MRC-5 and BJ human fibroblasts [216] Fenofibrate -Senescent T/C28a2 human chondrocytes [217] Cardiac glycosides -Therapy-induced senescent A549 lung cancer cells and SK-MEL-103 melanoma cells in vitro and in vivo [218,219] Several natural and synthetic compounds have been tested for their senescence-eliminating effects in a variety of disease models. The table summarizes the primary current preclinical evidence demonstrating the senolytic agent and the experimental model used.…”
Section: Senolytic Model/cell Line Referencementioning
confidence: 99%
“…Cardiac glycosides are emerging as powerful senolytic agents. Using high-throughput screening, Triana-Martínez and Picallos-Rabina et al, revealed that proscillaridin A, ouabain and digoxin have potent senolytic activity [218]. The authors induced senescence in A549 lung tumor cells (and other tumor types) using a variety of chemotherapeutic agents (bleomycin, doxorubicin, etoposide, gemcitabine, and palbociclib), followed by exposure to digoxin.…”
Section: Cardiac Glycosidesmentioning
confidence: 99%
“…Senolytics include the BCL‐2 family inhibitors Navitoclax (ABT‐263) (Zhu et al, 2016) and ABT‐737 (Yosef et al, 2016); the flavonoid fisetin (Yousefzadeh et al, 2018); combinations of tyrosine kinase inhibitors and flavonoids (e.g. dasatinib and quercetin; Zhu et al, 2015); FOXO4‐p53 interfering peptides (Baar et al, 2017); HSP90 chaperone inhibitors (Fuhrmann‐Stroissnigg et al, 2017); and other compounds such as piperlongumine (Wang et al, 2016) and cardiac glycosides (Guerrero et al, 2019; Triana‐Martínez et al, 2019). Senolytics have emerged as promising agents for treatment of pulmonary fibrosis, atherosclerosis, osteoarthritis, type 1 and 2 diabetes mellitus, and neurocognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac glycosides and their cardenolide precursors were prominent among these novel pharmacological classes. These molecules, which inhibit Na + /K + -ATPase (Table 1 and Figure 2A), have a long clinical history in the treatment of congestive heart failure and atrial fibrillation and have recently attracted interest as potential anticancer molecules (Newman et al, 2008) and senolytics, i.e., selective inducers of senescent cell death (Triana-Martinez et al, 2019). Cardiac glycosides and cardenolides display a powerful WPB shortening effect and induce Golgi apparatus compaction (Figures 2B and 3A) instead of its fragmentation, suggestive of a novel WPB size-reducing mechanism.…”
Section: Screenmentioning
confidence: 99%